The Concept Of Fitrah In The Qur’an And Its Implications For Religious Behavior: Thematic Study Of Qs. Ar-Rum 30 Perspectivis On Tafsir Al Misbah - Muslan (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
ABSTRACT This study aims to analyze the concept of fitrah in the Qur’an, particularly in QS. Ar-Rum 30, and to examine its implications for religious behavior through a thematic approach based on Tafsir Al-Misbah. The research seeks to provide a comprehensive understanding of fitrah as a foundational concept that shapes human religiosity, both at the level of belief and practice. This study employs a qualitative approach with a literature study design. The primary data source is Tafsir Al-Misbah, supported by other classical exegeses such as Tafsir Ibnu Katsir and Tafsir At-Tabari. Secondary data are derived from relevant journal articles, books, and scholarly works. Data collection was conducted through documentation techniques, while data analysis utilized thematic analysis to identify, categorize, and interpret key concepts related to fitrah and its implications. The validity of the data was ensured through source triangulation and critical analysis of authoritative references. The findings reveal that fitrah is a multidimensional concept encompassing theological, anthropological, and ethical dimensions. It is understood as an inherent divine predisposition that directs humans toward tawhid while simultaneously functioning as a normative framework guiding religious behavior. The study further indicates that the actualization of fitrah is not automatic but depends on processes of internalization through education, environment, and spiritual awareness. Authentic religious behavior emerges when individuals successfully integrate cognitive, affective, and practical dimensions rooted in fitrah. Conversely, deviations in religious conduct reflect disruptions in this process. The implications of this study highlight the importance of developing a contextual and transformative understanding of fitrah in shaping religious behavior. It suggests that religious education should emphasize not only textual comprehension but also the internalization of values that foster balanced, moderate, and meaningful religiosity in contemporary society. Keywords: Fitrah, Qur’an, religious behavior, thematic interpretation.